ANALISA PENYEBAB HILANG SIRKULASI LUMPUR PADA PEMBORAN SUMUR X LAPANGAN Y - Pradiko Pradiko.Z.H; abdul hamid; puri wijayanti (Jurusan Teknik Perminyakan Fakultas Teknologi Kebumian dan Energi Universitas Trisakti, 2017)
Lost circulation is one of the major problems in the drilling operation which can lead to not obtaining cutting, stuck pipe, and blow out. Therefore, lost circulation must be addressed because it has a high risk can increase the cpst and time during the drilling process. In general, there are several techniques that can be used to overcome the loss of circulation, one which is the use LCM (lost circulating material).In this thesis will investigate the loss circulation of drilling mud in the X well. The spud process in X well was started in March 2nd 2013, and reached total depth at 8950 ftMD. Drilling process has breakhtrough Lidah, Kawengan, Wonocolo, Ngrayong, and Tuban Karbonat formation and lost circulation was happen in Tuban Karbonat formation. Mud that used in this job was oil base mud and changed to KCL polymer when drilling into production zone.The cause of lost circulation taht occurs in X well because of the formation which has pores large of particle size, so that the mud flow into the formation and pressure in the hole is greater than the formation pressure. The controlling method which is used to handle the problem is using LCM which is Calsium Carbonate (CaCO3) and do Blind Drilling.